Manajemen Program Komisi Pelayanan Anak dalam Pembentukan Spiritualitas Anak Sekolah Minggu - Polak, Nancy Eva (Tumou Tou, 2023)
The purpose of this study was to analyze the Children Service Comission (CSC) management of Sunday School kids building spirituality at GMIM Elim Papakelan. Data were collected through observation, interviews and literature study. From the results of the data analysis, the researchers found that: (1) parents play an important role in the formation of the spirituality of Sunday school children. (2) parents act as primary teachers to teach about Christ and His teachings to children. (3) the role of parents to be an example and role model for children. (4) Lazy and negligent parents appear in their behavior that does not play an active role in the formation of children's spirituality, which becomes an obstacle in the formation of children's spirituality. (5) in everyday life parents have not been a good example to be imitated by children. (6) lack of time with children for working parents. (7) teaching and reminding parents through church sermons and special visits is the pastor's effort to play a role in the formation of children's spirituality. (8) the efforts of Sunday school teachers to hold creative programs to attract children to participate in Sunday school activities and include parents in them. (9) parents try to improve themselves in order to be a good example for children. (10) maximize time with children.